Acquired partial lipodystrophy associated with varicella - Kurugöl, Zafer; Ulger, Zülal; Berk, Omer; Tuğral, Okan (The Turkish Journal of Pediatrics, 2009)
Acquired partial lipodystrophy (Barraquer-Simons syndrome) is a rare condition with onset in childhood, and it is characterized by progressive loss of subcutaneous fat in a cephalocaudal fashion. Although it is known that acquired partial lipodystrophy usually follows acute febrile illness, it is very rarely reported to occur in association with varicella. In this case report, we present a seven-year-old girl with progressive loss of fat in her face just after varicella who was diagnosed as acquired partial lipodystrophy.